FINANCIAL AND ECONOMIC INDICATORS AND RESULTS OF HIGHER EDUCATION INSTITUTIONS (American Journal of Interdisciplinary Research and Development, 2024)
This article examines the financial and economic factors and results of the development of higher education institutions today.